FLAME-ATOMIC ABSORPTION SPECTRO PHO TOMETRIC DETERMIN A TION OF TRACE METALS IN URINE: Short Communication (Biological Sciences - PJSIR, 2002)
) The levels (µg 1·1 of cadmium , copper, lead, manganese and nickel in the urine of selected students of Lagos State University, Ojo, were determined by flame-atomic absorp tion spectrophotometry. These levels were compared with control urine samples collected from some randomly selected rural dwellers in Ejigbo, Osun State. The samples were digested and analyzed following standard methods of urine analysis. The trace metals in the urine of students were found to be higher than those in the urine of the rural dwellers. The results revea led sta tist ically significa difference in the Cd, Cu, Mn, and Pb levels between the control samples and those collected from the  students.